The social market economy: an export for the Third World? - Karl Fasbender; Manfred Holthus (Intereconomics, 1990)
Long before the socialist industrialized nations began to call their centrally planned, or government controlled, economies into question, policymakers in many developing countries with dirigistic, interventionist systems, including capitalist oriented ones, had started to rethink their economic philosophies. Now that the former exporters of the concept of the centrally planned economy are themselves interested in importing free-enterprise ideas, reform in the Third World is likely to take on more momentum and interest in the social market economy will increase.
Keywords: 330; Economic Systems